Molecular Insights of Diabetic Complications and Future Targets for Therapy - Putta, Swathi; Kilari, Eswar Kumar (Asian Journal of Biological and Life Sciences, 2020)
In Diabetes, hyperglycemia, insulin resistance, oxidative stress and inflammation are the known associates for the loss of β cell function. Indeed, number other factors influencing many other molecular mechanisms are involved in the progression of microvascular and macrovascular complications. This review focused on the putative mechanism such as polyol pathway, hexosamine pathway, PKC, AMPK and MAPK pathways; AGEs, GLP -1, GIP, DPP4, 11β HSD1, DGAT2, SGLT2, HSP, TXNIP and SCD; the role of cytokines, adipokines and growth factors; role of GPCRs and other receptors like SUR, HCA2 and MTR; the role of autophagy and epidemic factors involved in diabetes and associated complications.
Keywords: Diabetes; Diabetic Complications; Hyperglycemia; Insulin Resistance; Molecular mechanisms